Risk-sharing agreements for medical devices: a stakeholder-based qualitative study in Czechia - Hospodková, Petra; Rogalewicz, Vladimír (Frontiers in Public Health, 2025)
ObjectiveThe rising costs and uncertain clinical value of innovative health technologies have spurred growing interest in alternative reimbursement models, particularly outcome-based risk-sharing agreements. While such models are increasingly discussed and applied in the pharmaceutical sector, their use in the context of medical devices remains limited and underexplored, despite similar challenges regarding evidence generation and financial risk. This qualitative study examines stakeholders’ perspectives and identifies key barriers to the implementation of outcome-based agreements for medical devices.MethodsA qualitative design was employed, based on 16 semi-structured interviews with stakeholders from payer organizations, providers, regulatory authorities, and the medical device industry. Interview transcripts were thematically analyzed based on the inductive coding principle.ResultsParticipants most frequently reported three dominant barrier domains: regulatory and legal uncertainty, weak infrastructure for real-world outcome measurement, and institutional reluctance to engage in shared-risk models. Nevertheless, respondents acknowledged the conceptual benefits of outcome-based agreements and supported the idea of small-scale pilot programs in selected high-cost therapeutic areas.ConclusionEnabling broader adoption of such models requires not only regulatory and institutional evolution but also targeted investment in data infrastructure. In particular, the capacity to generate and interpret real-world evidence through Big Data analytics will be crucial for supporting sustainable, transparent, and evidence-based reimbursement decisions in the medical device sector.